Clinical and sociodemographic characteristics of HIV/AIDS patients with neurological complications due to opportunistic infections at the Hospital Nacional Hipólito Unanue, 2017-2019 - Espinoza Pérez, Susel (2022)
Objective: To describe the clinical and sociodemographic characteristics of HIV/AIDS patients with neurological complications due to opportunistic infections at the Hospital Nacional Hipólito Unanue in Lima, Peru (2017-2019). Materials and methods: An observational, descriptive, cross-sectional and retrospective study was conducted with medical records of patients older than 18 years diagnosed with HIV/AIDS and neurological complications due to opportunistic infections. The study variables were analyzed with descriptive statistics using the IBM SPSS Statistics V25. Results: Forty-five (45) medical records were analyzed: the average age was 34.38 ± 11.19 years, 73.30 % were males, 31.10 % were from the district of Ate, 53.30 % completed secondary education, 24.40 % were unemployed, 67.90 % (n = 19/28) were heterosexual and 17.20 % had tuberculosis as comorbidity. The most common clinical manifestations were headache (21.30 %) and impaired consciousness (19 %). Cerebral tuberculosis and neurotoxoplasmosis were the most frequent neurological complications (30.90 % in both cases). Eighty-three point three zero percent (83.30 %) (n = 25/30) of the study subjects had a viral load > 100,000 copies/ml, 97.40 % (n = 38/39) had a CD4 count < 199 cells/mm3, and 90.50 % (n = 38/42) showed poor adherence to HAART. Conclusions: Neurological complications due to opportunistic infections most frequently affected the age group of 18 to 30 years old, males, unemployed and heterosexuals. The most frequent complications were cerebral tuberculosis and neurotoxoplasmosis. Most of the study subjects had a viral load > 100,000 copies/ml, CD4 count < 199 cells/mm3 and poor adherence to HAART.